Identification of species of the genus Meloidogyne in cucurbits: Distribution and occurrence in Arequipa, Peru - Miranda-Barrios, Elizabeth (2020)
Cucurbitaceae contribute to the diet of the population, as well as to the economy of farmers; but are harmed by phyto-parasites like to Meloidogyne spp. The know about the root-knot nematode is empty to put suitable strategies to management. The objectives of this research were identified species of Meloidogyne genera in cucurbitaceaes and determine their distribution and occurrence in Arequipa, Peru. Roots of Cucurbita maxima, Citrullus lanatus, Cucumis melo and Cucurbita pepo were collected, identifying them by electrophoresis for the enzyme esterase. Meloidogyne spp. is present in 87.1% from places that were evaluated and M. incognita I1 (Rm: 1.00), M. incognita I2 (Rm: 1.02 - 1.07), M. incognita S2 (Rm: 0.87), M. arenaria A1 (Rm: 1.19), M. arenaria A2 (Rm: 1.19 - 1.25), M. hapla H2 (Rm: 0.95) and one specie atypical of Meloidogyne (Rm: 0.87) were identified with occurrences of 17.14%, 42.86%, 2.86%, 17.14%, 2.86%, 11.43% y 5.71% respectively.